Copper-based catalysts supported on nitrogen-doped reduced graphite oxide for dehydrogenation of cyclohexanol to cyclohexanone - Mageed, Alyaa Khadhier (2017)
Copper based catalysts have industrial importance in different hydrocarbons reactions especially in the synthesis of cyclohexanone from dehydrogenation of cyclohexanol. Fast deactivation of the copper based catalysts at operating conditions is one of the significant problems in the industrial process. The objectives of the present work are to formulate the catalyst support (nitrogen doped reduced graphite oxide N-rGO) and two types of the supported catalysts namely supported copper (Cu/N-rGO) and supported tri metals alloy (CuNiRu/N-rGO) in paper forms, to analyse the properties of the synthesised catalyst support (N-rGO) and the synthesised catalysts as well as to investigate the catalytic performance of the two supported catalysts in the dehydrogenation of cyclohexanol to cyclohexanone, to evaluate the suitable kinetics and model that represents the catalysts behaviour in the dehydrogenation of cyclohexanol to cyclohexanone. All experiments on the catalytic performance were conducted at moderate temperatures (200-270oC) and at 1 atm. The support and the catalysts were synthesised using chemical reduction of the graphite oxide (GO) in NH4OH solution followed by a thermal treatment with N2. The morphological, structural, chemical, surface, thermal and crystallinity analyses as well as phase determination were performed. The performances of the catalysts were evaluated in the gas phase dehydrogenation of cyclohexanol to cyclohexanone. The reaction was performed in a fixed bed reactor. The products and by products of the process were analysed using the gas chromatography (GC). N-rGO provides more than 63% surface area based on BET analysis than that provides by GO. Moreover, N-rGO is thermally more stable than GO by 40oC. Single catalyst (Cu/N-rGO) showed dispersion of the metal particles with diameter approximately ranged from 5 nm to 50 nm and trimetallic catalyst (CuNiRu/N-rGO) has a particle size in the range of 1 nm to 10 nm. CuNiRu/N-rGO catalyst has bigger surface area up to 75% compare to Cu/N-rGO. In Addition, CuNiRu/N-rGO catalyst exhibits better thermal stability. After reaction, the detected particle sizes ranged from 5 nm to 20 nm for the CuNiRu/N-rGO catalyst and 100 nm to 200 nm for Cu/N-rGO catalyst. The conversion of the cyclohexanol using CuNiRu/N-rGO is 4% higher than using the Cu/N-rGO. The selectivity for cyclohexanone in case of the Cu/N-rGO catalyst is about 83.88%, whilst, the CuNiRu/N-rGO showed approximately 6% better performance. The yield of the cyclohexanone using the Cu/N-rGO is about 78%, while with the improvement of the Cu/N-rGO by adding the Ni and Ru as promoters the yield of cyclohexanone was improved by 8%. The significant improvement posed by the CuNiRu/N-rGO is the duration of the steady state period that was proposed up to 7 times (from 60 minute to 380 minute). CuNiRu/N-rGO performs much better in terms of higher conversion, better selectivity, longer steady state period and better resistance for deactivation. The kinetics behaviour was fitted based on the Langmuir-Hinshelwood (L-H) models presented with different mechanisms models. Using fitting techniques, the single active site mechanism of the H2 adsorption and its dissociation on the surface reaction suits the experimental data for Cu/N-rGO catalyst. However, the H2 adsorption without dissociation on the surface reaction mechanism suits CuNiRu/NrGO catalyst better. This indicates that the catalyst exhibit dual active site mechanism. This research shows that the N-rGO has the potential to be an excellent support due to its excellent flexible interstices that provide the macro and microporous active catalytic sites. Furthermore, this study shows that the CuNiRu/N-rGO catalyst provides the suitable and selective active sites for the dehydrogenation of cyclohexanol to cyclohexanone reaction.